MANAJEMEN BERBASIS NILAI RELIGIUS: BUDAYA SHOLAT DHUHA DAN MEMBACA AL QUR’AN DI MA AL-CHALIL DAN SMP ISLAM TERPADU AL-CHALIL TONTONG SUIT - Mahsur, Mahsur (Universitas Islam Madura, 2024)
This study aims to explore and analyze the implementation of religious value-based management through the culture of dhuha prayer and reading Surah Al-Waqiah at MA Al-Chalil Tontong Suit and Integrated Islamic Junior High School Al-Chalil Tontong Suit. This research uses a descriptive method with a qualitative approach. The location of this research is at MA Al-Chalil Tontong Suit and SMP Islam Terpadu al-Chalil Tontong Suit. Data collection in the study was carried out by observation, interview, and documentation. Informants in this study include: Principal, Vice Principal, Teachers and students. The data analysis technique used in this study used the Miles and Huberman interactive data analysis model. To measure the validity of the data in this study, researchers used triangulation techniques. The triangulation used in this research is source triangulation by using cross-checking data between informants. The results showed that the implementation of this program relies heavily on the active involvement of teachers and school staff, who are not only facilitators but also real examples for students. The role of teachers as mentors in this activity helps students internalize the values taught, so that religious values become part of their daily lives. The religious value-based management applied at MA Al-Chalil and Al-Chalil Integrated Islamic Junior High School has succeeded in creating a harmonious educational environment, which focuses not only on intellectual but also spiritual development, producing a generation with noble character and achievements.